A multi-modal fundus image based auxiliary location method of lesion boundary for guiding the layout of laser spot in central serous chorioretinopathy therapy. (March 2023) - Xu, Jianguo; Shen, Jianxin; Jiang, Qin; Wan, Cheng; Zhou, Fen; Zhang, Shaochong; Yan, Zhipeng; Yang, Weihua
Abstract: The lesion boundary of central serous chorioretinopathy (CSCR) is the guarantee to guide the ophthalmologist to accurately arrange the laser spots, so as to enable this ophthalmopathy to be treated precisely. Currently, the accuracy and rapidity of manually locating CSCR lesion boundary in clinic based on single-modal fundus image are limited by imaging quality and ophthalmologist experience, which is also accompanied by poor repeatability, weak reliability and low efficiency. Consequently, a multi-modal fundus image-based lesion boundary auxiliary location method is developed. Firstly, the initial location module (ILM) is employed to achieve the preliminary location of key boundary points of CSCR lesion area on the optical coherence tomography (OCT) B-scan image, then followed by the joint location module (JLM) created based on reinforcement learning for further enhancing the location accuracy. Secondly, the scanning line detection module (SLDM) is constructed to realize the location of lesion scanning line on the scanning laser ophthalmoscope (SLO) image, so as to facilitate the cross-modal mapping of key boundary points. Finally, a simple yet effective lesion boundary location module (LBLM) is designed to assist the automatic cross-modal mapping of key boundary points and enable the final location of lesion boundary. Extensive experiments show that each module can perform well on its corresponding sub task, such as JLM, which makes the correction rate (CR) of ILM increase to 92.11%, comprehensively indicating the effectiveness and feasibility of this method in providing effective lesion boundary guidance for assisting ophthalmologists to precisely arrange the laser spots, and also opening a new research idea for the automatic location of lesion boundary of other fundus diseases. Graphical abstract: Image 1 Highlights: The JLM is established to boost the accuracy of ILM in locating the key boundary points of CSCR lesion area and make up for its defect of insufficient generalization. The SLDM is designed to detect the scanning lines on the SLO images, avoiding the dilemma of directly locating the lesion area using traditional image processing techniques. The LBLM is constructed to achieve the cross-modal mapping of the key boundary point positions of the lesion area and locate the CSCR lesion boundary on the SLO image. The proposed method innovatively achieves accurate and fast location of the CSCR lesion boundary, which is of great significance for more precise laser treatment of CSCR.